Behaviourally-informed household communications increase uptake of radon tests in a randomised controlled trial - Shane Timmons; Pete Lunn (The Economic and Social Research Institute (ESRI), 2023)
Exposure to radon gas is a leading cause of lung cancer. Testing homes for the gas is straightforward, yet most people do not undertake tests even when offered freely. We report a pre-registered randomised controlled trial of communications to encourage test uptake. Households (N = 3,500) in areas at high risk of radon exposure were randomly assigned to receive (i) a the control letter from the national Environmental Protection Agency; (ii) a behaviourally-informed version of the control letter that incorporated multiple nudges, including reciprocity messages and numeric frequencies of risk; (iii) this same behaviourally-informed letter in a re-designed envelope; (iv) the behaviourallyinformed letter in the re-designed enveloped with a radon risk map of the household's county. The behaviourally-informed letter led to a large increase in test uptake, from 22% in the control condition to 33% (a 50% increase). There was no additional benefit of the re-designed envelope, which generated uptake of 30%. Including the map led some households to respond faster, but the overall uptake (26%) was weaker. The results have implications for public health communications with households and show the potential for techniques from behavioural science to help mitigate environmental risks.
Keywords: 330; radon; nudge; environmental risks; randomised controlled trial; experiment; behavioural public policy